Techno-Economic Feasibility Assessment for the promotion of Grid-Connected Rooftop PV Systems in Botswana: A Case Study - Kassem, Youssef; Gokcekus, Huseyin; Agila, Fadel Ali Ramadan (Engineering, Technology & Applied Science Research, 2023)
The main aim of the present study is to investigate the solar energy potential and evaluate the economic viability of a 5kW grid-connected rooftop photovoltaic (PV) system as an electricity generation source in three selected regions (Gaborone, Maun, and Tshabong) in Botswana for the first time. In this study, NASA POWER data were used for evaluating the solar potential in the selected regions. The results showed that the selected locations are suitable for the installation of various scales of PV systems due to the high global horizontal solar radiation. RETScreen Expert software was used to assess the techno-economic feasibility of the proposed systems. The performance of the proposed systems with various PV technologies (mono-crystalline silicon and poly-crystalline silicon) is analyzed. Furthermore, economic and financial indicators such as net present value, annual life cycle savings, payback, benefit-cost ratio, and cost of energy production were calculated. The results indicate that the proposed system is very promising for all the selected locations. Additionally, it was found that the PV projects with poly-Si technology produced a large amount of energy and have a low electricity cost compared to mono-Si technology. The results suggest that grid-connected rooftop PV systems have a significant role in covering the electricity demand and in reducing carbon dioxide emissions, especially in high population density and rural regions. This study provides some useful recommendations for decision-makers regarding the development and deployment of PV energy technology in Botswana.